LITERASI KEUANGAN BAGI UMKM: Laporan Keuangan Untuk Pengembangan Usaha UMKM - Asep Risman; Matrodji Mustaffa (Jurnal Abdimas Perbanas, 2023)
Micro, Small, Medium Enterprises (MSMEs) are an important part of the country's economic activities, especially during this COVID-19 pandemic because MSMEs are flexible and do not require large capital. MSMEs absorb excess labor from the formal business sector which is closed as a result of the COVID-19 pandemic. DKI Jakarta and Lampung have many Micro, Small, Medium Enterprises (MSMEs) and are the focus of employment, especially those affected by layoffs due to the COVID-19 pandemic and driving the economy during and after the COVID-19 pandemic. The classic problems faced by MSMEs are generally related to capital and marketing. The Master of Management Study Program, Faculty of Economics and Business, Mercu Buana University (FEB-UMB) in collaboration with the University of Lampung (UNILA) took the initiative to improve the financial literacy of MSMEs in Jakarta and Lampung. This PKM activity was attended by 39 people who are owners and managers of MSMEs in DKI Jakarta and Lampung. The form of this activity is to provide training to increase knowledge in financial statement analysis. It was opened directly by the Chancellor of UMB, Prof. Dr. Ngadino Surip, as well as presenting speakers from Unila, Prof. Mahrinasari Through this community service activity, it is hoped that it can help MSMEs in Jakarta and Lampung have the ability to obtain funding from creditors so that capital problems can be overcome and MSMEs are increasingly contributing to economic growth and employment.